Children and police questioning: A rights-based approach - Forde, Louise (Criminology & criminal justice, 2024)
Under the United Nations Convention on the Rights of the Child, children in conflict with the law are entitled to dignity and respect for their rights within a youth justice system adapted to their age and circumstances. The United Nations Convention on the Rights of the Child recognises the necessity of ensuring that children’s rights are protected during the criminal process, emphasising the importance of legal advice, information and support to enable their participation in the process. Police questioning can be a particularly difficult experience for children, given their vulnerability and immaturity and yet it can have very serious consequences for children. This article examines the rights of the child during police questioning, from the perspective of children themselves. Presenting the findings of a study of children’s experiences of their rights when being questioned by the police (An Garda Síochána) in Ireland, the article highlights the need to adapt police questioning processes to the needs and circumstances of the child, while emphasising the powerful case for greater involvement of children in research about criminal justice and policing so that their experiences of their rights can be better understood.